Rational prediction of pharmacological treatment options for a novel KCNH2- linked variant of the Short QT Syndrome - Jules C Hancox; A Graham Stuart (Annals of Circulation - Peertechz Publications, 2018)
Congenital disorders of cardiac repolarization are associated with risk of serious arrhythmias and sudden death. The Long QT Syndrome (LQTS) is well-established to predispose towards torsades de pointes [1]. The Short QT Syndrome (SQTS) is a more recently discovered condition involving abbreviated repolarization that predisposes to atrial and ventricular arrhythmias and sudden death [2]. It is characterized by short QT intervals on the electrocardiogram, frequently with tall upright T waves and by a poor rate adaptation of the QT interval: short QT intervals persist even at slow heart rates [2-4]. Due to the risk of sudden death, SQTS patients are often treated with implantable cardioverter defi brillators (ICDs). Mutations to genes that encode critical components of cardiac potassium channels have been implicated in the syndrome: KCNH2 in SQT1, KCNQ1 in SQT2 and KCNJ2 in SQT3 [2-4]. Of successfully genotyped cases, the most prevalent mutations affect KCNH2 [3]. KCNH2 (alternative nomenclature hERG: human-Etherà- go-go-Related Gene) is responsible for encoding the pore-forming protein of channels that mediate the cardiac rapid delayed rectifi er current, IKr [5]. IKr is vital for normal ventricular repolarization, evidenced by the fact that lossof- function mutations in hERG-mediated subunits underpin the LQT2 form of congenital Long QT Syndrome [1,5]. Gainof- function mutations in hERG-mediated subunits underpin variant 1 (SQT1) of the SQTS [2,3]....